(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The present study was undertaken to find out the effectsof student-centered counselling on low-achievers in secondary schcols. Sinceacademic achievement is intimately linked with such factors as study habits,academic motivation and self -concept, the effects of counselling not only onacademic achievement but also on these other factors have also been analyzedinto their important components, and special care has been taken to tackle themost frequent among them during the counselling.